Influence of high performance work systems on employee subjective well-being and job burnout: empirical evidence from the Chinese healthcare sector - Fan, David; Cui, L.; Zhang, M.; Zhu, C.; Hartel, C.; Nyland, C. (Routledge, 2014)
Over the last two decades, high performance work systems (HPWSs) research has been dominated by examining the effects of these systems on firm performance. Research on the impact of HPWSs on employees has been marginalised. This study examines the impact of HPWSs on two psychological outcomes for employees, namely, subjective well-being (SWB) and workplace burnout, by utilising data collected from 1488 physicians and nurses in 25 Chinese hospitals. It also examines the moderating effects of employees’ organisational based self-esteem (OBSE), as an individual intervention and physician–nurse relationships, as an organisational intervention, on the relationship between HPWSs and employee outcomes. HPWS is found to increase employees’ SWB and decrease burnout. Such well-being-enhancing and burnout-relieving effects are stronger when employees have high OBSE. The positive effect of HPWS on SWB is also stronger when there is a collaborative relationship among employees in an organisation. The major contribution of this study is to unpack the ‘black box’ of how HPWS influences employee well-being in the Chinese healthcare sector context.